Periconceptional stressors and social support and risk for adverse birth outcomes - Kari A. Weber; Suzan L. Carmichael; Wei Yang; Sarah C. Tinker; Gary M. Shaw; National Birth Defects Prevention Study (BMC, 2020)
Abstract Background The prevalence of preterm birth and low birth weight has been increasing slightly in recent years. A few studies have suggested that psychosocial stress during pregnancy may increase risk for these adverse birth outcomes. To extend those observations, we analyzed various major life event stressors separately and cumulatively as potential risk factors for preterm birth and low birth weight using granular categories of each outcome in a large, population-based study. Additionally, we assessed if greater social support buffered any effects. Methods Data were from a nested prevalence study of 4395 women in the National Birth Defects Prevention Study who delivered live-born non-malformed infants (controls) between 2006 and 2011. Participants completed a standardized, computer-assisted interview between 6 weeks and 24 months after delivery that included questions on stress and social support from 3 months before pregnancy to the 3rd month of pregnancy. Cumulative stress and support indices were also calculated. Preterm birth was divided into "early preterm" (< 32 weeks), "late preterm" (32-36 weeks) and "term." Low birthweight was divided into "very low birth weight" (< 1500 g), "low birth weight" (1500-2499 g) and "normal birth weight" (≥2500 g). Relative risks and 95% confidence intervals (95% CI) were calculated using Poisson regression. Results For women reporting relationship difficulties, there was a suggestive risk of early preterm birth (RR: 1.9, 95%CI: 0.9-3.9) and very low birthweight (RR: 2.0, 95%CI: 0.9-4.4). For women reporting that they or someone close to them were victims of abuse, violence, or crime, there was an increased risk of low birthweight (RR: 1.8, 95%CI: 1.1-2.7) and late preterm birth (RR: 1.5, 95%CI: 1.0-2.2). There were no strong associations observed between social support questions and the various outcomes. Conclusions Our results add some support to prior evidence that certain stressors may be associated with increase selected adverse birth outcomes risk. We did not find strong evidence that social support buffered the observed risks in our study.